Expansion of maize seed systems research to the retail space - CGIAR Research Program on Maize (2019)
Agro-dealers were one of the key information outlets about maize seed varieties. Seed company engagement with agro-dealers and in-store promotions (push marketing) should be further explored to improve returns on investments in seed systems.